PENGUKURAN FREKUENSI NATURAL PADA GEDUNG BERTINGKAT MENGGUNAKAN ACCELEROMETER GPL-6A3P - Wahyuni, Ayusari (JFT: Jurnal Fisika dan Terapannya, 2014)
This research has been carried out in multi-storey buildings by measuring natural frequencies on the building and its basic land. The recorded vibration data were analyzed with the H / V technique to get its natural frequency value. The measurement results of building floor vibrations using the GPL-6A3P accelerometer show that the natural frequency on the 3rd floor and 2nd floor is 2 Hz, while on the 1st floor is 0.6 Hz and on the subgrade of the building is 0.4 Hz.